2012
DOI: 10.1186/1471-2474-13-88
|View full text |Cite
|
Sign up to set email alerts
|

I-ONE therapy in patients undergoing total knee arthroplasty: a prospective, randomized and controlled study

Abstract: BackgroundTotal knee arthroplasty (TKA) is often associated with a severe local inflammatory reaction which, unless controlled, leads to persistent pain up to one year after surgery. Standard and accelerated rehabilitation protocols are currently being implemented after TKA, but no consensus exists regarding the long-term effects. Biophysical stimulation with pulsed electromagnetic fields (PEMFs) has been demonstrated to exert an anti-inflammatory effect, to promote early functional recovery and to maintain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…However, grade IV OA outpatients could become candidates for joint replacement and be considered end-stage patients if their pain was to exceed 70 cm according to the VAS, as severe pain usually leads to total joint replacement [69]. This could be accompanied by an increase in mTOR and proinflammatory cytokine gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, grade IV OA outpatients could become candidates for joint replacement and be considered end-stage patients if their pain was to exceed 70 cm according to the VAS, as severe pain usually leads to total joint replacement [69]. This could be accompanied by an increase in mTOR and proinflammatory cytokine gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Local joint swelling, inflammation, and pain following THA and TKA are factors affecting patient recovery and joint function [44,45]. Holm et al .…”
Section: Non-surgical Interventionsmentioning
confidence: 99%
“…23,24 Pulsed electromagnetic fields (PEMFs) is a safe and non-invasive modality to reduce joint swelling and inflammation, the need for NSAIDs and the time to functional recovery through its effect on the IBRAHIM ALAzzAWI NIzAM HADDAD An evidence-BAsed review of enhAnced recovery interventions in Knee replAceMent surgery A 2A receptors of inflammatory cells. 24,25 Many studies have demonstrated the effect of PEMFs following knee surgery.…”
Section: Pulsed Electromagnetic Fieldsmentioning
confidence: 99%